Coordinating urban construction and coal resource mining based on equilibrium value between coal reserve and land resource in coal cities. Issue 1 (1st January 2021) - Jiang, Dongmei; Li, Xiaoshun; Wang, Yuexiang; Bian, Zhengfu; Zhang, Jian; Huiping, Fan
Abstract: With the acceleration of urbanization and industrialization, coal cities in China are suffering from the conflicts between urban construction and coal mining (land- mining). Land-mining conflicts in coal cities have caused serious destruction of land resources and the aggravation of ecological and economic conflicts. In order to deal with the land-mining conflict, we proposed a new three-dimensional spatial analysis framework to overall plan the underground coal exploitation and aboveground land use based on economic comparative advantage and value equilibrium theory. First, estimating aboveground land resource value (LP) and underground coal resource value (MP), then comparing MP and LP by equilibrium analysis method to recognize three-dimensional development boundary. Last three boundaries derived were used to divide the study area into four parts (construction/mining-forbidden area, construction put-off/mining-limited area, construction limited/mining-put-off area and construction forbidden/mining area). Ji'ning, a typical Chinese land-mining conflict city, is taken as a case to verify the effectiveness of the new method. The results show that the amount of coal mining and urban construction area increased by about 2 times, the new method can resolve land-mining conflicts in coal cities. It can contribute to a better reference for the design of coal city regulation and control policies design.